IMPROVING STUDENTS’ VOCABULARY MASTERY BY USING FAST HANDS GAME AT THE SECOND GRADE STUDENTS OF SMPN 1 BAROMBONG - Sinta Dewi Anggung; Nur Ima (EDU RESEARCH, 2023)
This research aimed at finding out the improvement of students’ vocabulary mastery by using Fast Hands Game. This research used a pre-experimental method. The population of this research was the second grade students of SMPN 1 Barombong. The total sample was 26 students and it used a purposive sampling technique. In collecting data, the researcher used vocabulary test that is administered of pre-test and post-test. The result of this research showed that the mean score in post-test was higher than the mean score in pre-test (80,54 > 46,73). The result of t-test was greater than the t-table value (13,38 > 2,060) at the significance level of 0,05. Based on the result of data analysis, it is concluded that using Fast Hands Game can improve the students’ vocabulary mastery at SMPN 1 Barombong.